فاعلية برنامج تدريبي قائم على نادي الفضاء في تنمية الخيال لدى الأطفال - محمد، صلاح محمد محمود (رابطة التربويين العرب, 2016)
هدفت هذه الدراسة إلى الكشف عن فاعلية برنامج تدريبي قائم على أنشطة نادي الفضاء في تنمية الخيال لدى تلاميذ الصف السادس الابتدائي، وتكونت عينة الدراسة من عدد (12) تلميذاً وتلميذة (6) ذكور، ومثلهم من الإناث، طبق عليهم الباحث المنهج شبه التجريبي ذو المجموعة الواحدة ذات القياس القبلي والبعدي، وكانت أدوات الدراسة المستخدمة عبارة عن اختبار الذكاء المصور، مقياس المستوى الاقتصادي الاجتماعي، برنامج الدراسة، مقياس الخيال، وبعد المعالجة الإحصائية توصلت النتائج إلى فاعلية برنامج الدراسة في تنمية جميع أبعاد الخيال الستة (الوعي، التصور، أحلام اليقظة، الانسحاب من الواقع، المرونة، الاحتفاظ بالاتجاه)، وتوصلت النتائج أيضاً إلى وجود فروق دالة بين متوسطي رتب درجات القياس البعدي وما بعد المتابعة لصالح القياس بعد المتابعة في جميع أبعاد الخيال كذلك أوضحت النتائج عدم وجود فروق بين متوسطي رتب درجات الذكور والإناث.
This study aimed at recognizing the effectiveness of a training program based at the Space Club in the development of children's imagination. The study involves (12) grade-six pupils of which are (6) males and (6) females. The researcher used the semi-trial approach of one group of pre and after grading. The study tools were the pictured intelligence test, the economic and social status test, the study program, and the imagination test. Statistic filters were applied to find that the study programs effective in the development of all six dimensions of the imagination (Consciousness, Representation, Day dreams, withdrawal from reality, flexibility, Maintenance of direction).The results also show differences between the intermediate after-grading scores and those that follows in all of the imagination dimensions. Favoring follow up measurements Likewise it shows no differences between the average male and female scores.
Keywords: الأطفال -- الخيال -- نادي الفضاء